KARAKTERISTIK DEMOGRAFIS DAN HUBUNGANNYA DENGAN PENYAKIT TUBERKULOSIS DI PROPINSI JAWA TENGAH (ANALISIS LANJUT RISKESDAS 2007) - Girsang, Merryani; Tobing, Kristina (Media Penelitian dan Pengembangan Kesehatan, 2010)
Data of "Riskesdas " regarding the relation of the incident of tuberkulosis and demographic based on the infection of tuberkulosis in Central Java province has not been available. The purpose of this study is to identify how big is the spread of the lung-TB incidents from the family members who were interviwed in the Riskesdas 2007. Design of the study is crossectional, data is from Riskesdas 2007 reveals from 35 Districts in Central Java, based on the result of the interview from selected family member, who have the symptoms of cough more than 2-3 weeks, loss weight, sweat at night, and fever. Data is analysed by SPSS window version 15.0, and the result is presented in the frequency tabulation. The results show that from the 4380 population interviwed, 953 respondent has ever been infected with baccili tuberculoses. The incident of TB in female is higher than male, 50.5% and 49.5 % respectively (OR=1.106; 95CI=0.944-1.295). Productive age group tend to be dominant, such as group of 35-65 years old are infected TB 20.1%, group of farmer 25.2%, whereas the group of respondent who has no job 17.6% (OR=1.233;95%CI=0.653-2.327). Labor and coolie are 22.0% have a risk to be infected with TB (OR=1.594;95%CI= 1.833-3.051), and based on the lengt of time working they have 1.5 times higher risk to be infected with TB. The study conclude that the TB is the direct infectious disease, the baccili can spread through the air which can be easily inhaled to the lung. Respondents who their family members or their neighbour have already been infected with TB will spread the disease as long as they are not treated properly.   Key words: Tuberkulosis, TB, Demografi.